Effects of different grades of rural reclaimed water irrigation and water levels on microbial community structure of rhizosphere soil in paddy field - Li, Yuanyuan; Xiao, Menghua; Zheng, Shizong (International Journal of Agricultural and Biological Engineering, 2025)
The composition of soil microbial community structure and the diversity of microbial population could reflect the quality of soil environment to a certain extent. In this paper, three kinds of irrigation water sources and three kinds of water level regulations were set to investigate the effects of different sources of reclaimed water irrigation and the regulation of irrigation and drainage on species diversity and microbial diversity in paddy fields, aiming to clarify the microbial mechanisms under rural domestic reclaimed water irrigation. Through five-point method on soil samples in 0-40 cm layers, the soil characteristic was tested by 16S rDNA amplicon sequencing. Results showed that the maximum biodiversity is observed under primary treated water of domestic sewage R1 in soil layers of 0-20 cm and 20-40 cm. In the surface layer (0-20 cm) of soil, irrigation with rural reclaimed water can significantly increase the microbial diversity. The soil has the largest number of microbial communities and the richest biological communities under secondary treated water of domestic sewage R2, while it was the smallest under river water CK water source irrigation. The relative abundance of Proteobacteria is highest in 20-40 cm soil, and the relative abundance of Proteobacteria and Acidobacteria in 0-20 cm soil can be significantly increased under R1 and R2 water source irrigation conditions, while the abundance of Firmicutes can be reduced. The relative abundance of Chloroflexi in 20-40 cm soil layer can be significantly increased with R2, while reducing the relative abundance of Acidobacter. Moreover, in the 0-20 cm soil, both the Chao1 index and Ace index showed significant differences (p<0.05) between R1 and CK, and between R2 and CK. In the 20-40 cm soil, the Shannon index showed a significant difference (p<0.05) between R1 and R2, and also the Simpson index in this soil layer showed a significant difference (p<0.05) between R1 and CK treatments. Therefore, reclaimed water irrigation can significantly increase the biodiversity and community richness of the rice field root zone. Under the same water source conditions, the higher farmland water level could increase the difference in microbial diversity. This research clarifies the microbial action mechanisms in irrigation with rural reclaimed water, providing a theoretical basis for its application in agricultural fields. Key words: physiochemical properties; bacterial community; species diversity; species abundance; high-throughput sequencingDOI: 10.25165/j.ijabe.20251806.8569Citation: Li Y Y, Xiao M H, Zheng S Z. Effects of different grades of rural reclaimed water irrigation and water levels on microbial community structure of rhizosphere soil in paddy field. Int J Agric & Biol Eng, 2025; 18(6): 135–143.